A study on improving the efficiency of non-isolated buck-boost bidirectional DC–DC converter. (2nd October 2022) - Jeon, Hyeonmin; Ji, Changmin; Hur, Jaejung
ABSTRACT: In battery-based systems such as hybrid electric propulsion system for ships that use electric propulsion and DC grid, bidirectional converters are often used as interfaces between high-voltage power sources and low-voltage batteries for the purpose of storing excess energy and the fields of application for bidirectional converters are steadily expanding. This study proposes a new bidirectional converter with a high voltage conversion rate and low switch voltage stress. The proposed converter allows current to flow between modules by adding only one capacitor compared to a conventional bidirectional converter. To check the effectiveness of the proposed method, PSIM software by Powersim co. Ltd. was used to perform simulation tests. It was confirmed that the high voltage conversion rate was 4 times that of a conventional bidirectional converter in step-up mode and 1/4 that of a conventional bidirectional converter in step-down mode. Therefore, low-voltage components, such as MOSFETs, GTOs, etc., can be applied in the DC–DC converters thanks to the 1/4 voltage that is required in each switching time.